Peso econômico das soluções projetuais nas habitações de interesse social: estudo de caso dos conjuntos habitacionais do Programa de crédito solidário em Belo Horizonte - Renata Alves Siqueira (2008)
Building costs are based directly from the characteristics of design solutions wich are determined on the first stage during the conception phase. Know the repercussion of each of the decisions into the cost variable from a solution, in other words, your economic value, is fundamental to help you to choose by the best alternatives, notby just concerning about the materials, but also the architectural conception that was adopted. The fact of not know the consequences of cost into a architectonic decisions and the lack of an fast instrument to evaluate those almost always make the designers adopt usual solutions,without a deep consideration, caused by a lack of time to do a better avaliation and by the fear of the building not be executed.Inside of this argument the work attempt to show the architectural characteristics of building considerate of low cost and presents a case study where the performances of cost are analyzed and compared, with the objective of appraising the efficiency of that solutions under theeconomic variable.